Trading against the crowd : - Summa, John F. (John Wiley & Sons, 2004)
Trading Against the Crowd is the first book to provide a comprehensive assessment of investor crowd psychology, offering valuable market timing tools and trading techniques, including: MetaStock and Trade Station system and custom indicator code; comparative statistical studies of CBOE, OEX, and equity-only put/call ratios; straightforward instructions for combining price triggers with sentiment indicators; a practical guide to understanding put/call ratios, short sales, investor surveys, newsletter opinion, and stock market news-flow intensity; how to use LEAP options as trading vehicles to avoid use of stop loss orders; use of put/call ratios for trading the Treasury bond futures market; and test results and evaluation of trading system performance.